Policy Perspectives of the Nepali Congress Party on Women and Children in Nepal - Prasain, Indira Devi; Dhakal, Ram Prasad (Four Star Multidisciplinary Research Journal, 2025)
This article examines the policy perspectives of the Nepali Congress (NC) on women and children in Nepal. The well-being of women and children has a direct impact on social and economic progress. As Nepal’s oldest and largest mainstream political party, the NC’s ideological foundation is rooted in liberalism, emphasising individual freedom, democratic governance, and fundamental rights. The study employs a qualitative approach, relying solely on secondary data from scholarly articles, books, party manifestos (specifically the 2022 Election Manifesto), and party statutes.The findings reveal that the NC possesses a comprehensive policy framework dedicated to the welfare and empowerment of women and children, consistent with its democratic socialist ideology and constitutional mandates. Key policy areas include commitments to inclusion and proportional representation across state structures, advocating for equitable citizenship rights, and ensuring 33% women’s representation within party structures from central to local levels. In health and education, the NC pledges universal free basic and secondary education, targeted support for marginalised groups, universal health insurance, free treatment for young children and the elderly, and extensive maternal and child health programs, including “Pregnancy to Death” and “Golden Thousand Days.” For economic empowerment and social security, initiatives include skills training and microcredit for women, a “from Cradle to Grave” social security system, and job creation with employment guarantees. Furthermore, the party demonstrates a strong commitment to protecting women and children from exploitation and abuse, focusing on human trafficking and child labour through strengthened legal frameworks and rehabilitation efforts.Despite these articulated commitments, the study highlights a significant gap between policy pronouncement and actual implementation. Challenges identified include a persistent patriarchal mindset leading to male-dominated high-level policy-making, weak enforcement of existing laws, insufficient resource allocation, and the enduring impact of traditional norms. Issues such as prevalent child labour linked to poverty and women’s disproportionate representation in vulnerable, informal employment underscore these implementation deficits.